Differences in housing price dynamics across cities: A comparison of different panel model specifications. (August 2016) - Oikarinen, Elias; Engblom, Janne
This study compares a conventionally used panel data model – that does not allow for regional variations in housing price dynamics – with panel models that let the dynamics differ across regions. We concentrate on examining the momentum dynamics and the reversion speed towards the fundamental price level. Based on data over 1988–2012, the results indicate that the regional differences are generally quite small in the Finnish market. Nevertheless, in several cities the dynamics differ significantly from those indicated by the baseline model that does not allow for regional variation. In addition, the long-term coefficient on income considerably varies across regions, the coefficient being greater in the more supply-constrained cities. The results indicate that the use of panel models that assume similar housing price dynamics across regions can lead to flawed conclusions being drawn.